Activation of Toll-Like Receptor 2 in Acne Triggers Inflammatory Cytokine Responses() - Kim, Jenny (J Immunol, 2002)
One of the factors that contributes to the pathogenesis of acne is Propionibacterium acnes; yet, the molecular mechanism by which P. acnes induces inflammation is not known. Recent studies have demonstrated that microbial agents trigger cytokine responses via Toll-like receptors (TLRs). We investigated whether TLR2 mediates P. acnes-induced cytokine production in acne. Transfection of TLR2 into a nonresponsive cell line was sufficient for NF-κB activation in response to P. acnes In addition, peritoneal macrophages from wild-type, TLR6 knockout, and TLR1 knockout mice, but not TLR2 knockout mice, produced IL-6 in response to P. acnes. P. acnes also induced activation of IL-12 p40 promoter activity via TLR2. Furthermore, P. acnes induced IL-12 and IL-8 protein production by primary human monocytes and this cytokine production was inhibited by anti-TLR2 blocking Ab. Finally, in acne lesions, TLR2 was expressed on the cell surface of macrophages surrounding pilosebaceous follicles. These data suggest that P. acnes triggers inflammatory cytokine responses in acne by activation of TLR2. As such, TLR2 may provide a novel target for treatment of this common skin disease.